Analisis Yuridis Pembagian Hartawarisan Berdasarkan Wasiat Di Bawah Tangan Dalam Perspektif Kepastian Hukum (Putusan Nomor 425/Pdt.G/2021/Pn Jkt.Pst) - Rayi Kharisma Rajib; Ahmad Haikal Manggabarani; Muhammad Faisal Firdaus (GLOBAL SCIENTS PUBLISHER, 2026)
Issues regarding the distribution of inheritance based on private wills still frequently cause tension in society. This occurs because wills are not made through authorized officials, so their legal validity is often questioned, especially during the evidentiary process in court. This study aims to determine the validity of private wills in the distribution of inheritance and analyze the judge's considerations in providing legal certainty in Decision Number 425/Pdt.G/2021/PN Jkt.Pst. This research uses a normative legal method with a statutory regulatory approach and a case study approach.The results indicate that private wills can still be used as a basis for the distribution of inheritance if they meet applicable legal requirements and do not conflict with inheritance provisions. However, their evidentiary strength is not as convincing as authentic wills, potentially leading to disagreements among other heirs. In Decision Number 425/Pdt.G/2021/PN Jkt.Pst, the judge assessed the consistency between the contents of the will, supporting evidence, and the testator's wishes before deciding the case. The judge's considerations are crucial in creating legal certainty and protecting the rights of disputing parties. Therefore, legal certainty regarding the distribution of inheritance based on a private will is greatly influenced by the strength of the evidence and the judge's assessment during the trial.